Your dissertation in education - Buckler, Scott; Walliman, Nicholas (London : SAGE Publications Ltd, 2016)
Are you struggling with your dissertation? Have you started too late and now you're panicking? Help is here! Your Dissertation in Education is a straight-forward, plain English guide to doing and writing your project. It will take you from start to finish, with practical and friendly advice on every page. This second edition includes: - A new Foundations section with the concepts and tools you need to get started - An expanded guide to methodology and writing about methods - A new chapter on mixed methods An essential companion on your dissertation journey, this book is ideal for students across education, including teacher training, early childhood and education studies. Scott Buckler is Principal Lecturer in the School of Education at Newman University (Birmingham). Nicholas Walliman is Senior Lecturer in the Faculty of Design, Technology and the Environment at Oxford Brookes University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Dissertations, Academic